Botanical Gardens, Port of Spain, Trinidad, B.W.I. - (:unkn) unknown (Y. De Lima and Co. Ltd., Trinidad, 2009)
A picture of a pond in the Rock Garden of the Botanical Gardens is surrounded by plants, trees and an assortment of stones.
Colour: Black and White; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Botanical gardens--Trinidad and Tobago; Rock gardens--Trinidad and Tobago; Ponds--Trinidad and Tobago; Plants--Trinidad and Tobago; Trees--Trinidad and Tobago